The Modern Dilemma: Navigating Work Life Balance - Karwa, Kushal (Journal of Psychology and Behavior Studies, 2025)
The idea of work-life balance evolved from an attractive goal to an essential requirement since the development of a modern, fast-paced global society. The defining boundaries between occupation and personal affairs remain in the background of current interpretations, emphasizing adaptable integration between these domains. Technology enables constant connectivity between people through global email and messaging applications and social media platforms, and this merges work boundaries with personal freedom boundaries. Remote work, alongside the demands of the gig economy, creates serious difficulties for professionals when they attempt to disconnect from work responsibilities. Employees face growing mental health challenges because they must manage several professional roles during this changing work environment. Work-related expectations of availability, deadline management, and competition requirements typically lead to mental and physical depletion. The excessive work demands for productivity result in difficulties to recharge, which leads to damage to both personal relationships and general health. The paper evaluates these issues by studying technical progress, changed work arrangements, and the rise of freelance work patterns. It presents concrete methods to maintain balance in personal life. In this technology-driven era, the author supports setting boundaries and practicing self-care combined with new definitions of success, which maintain lasting mental well-being while fueling creativity. The document provides concrete approaches professionals need to navigate toward work-life harmony that supports their professional achievements and personal satisfaction.